Simulation operations and line of balance: integrated tools for decision making (2011)
This article presents the joint implementation of operations simulation and balance lines as tools that contribute to improving the efficiency of construction project planning, where its integration has been scarce at national and international level. The article exposes the results of the simulation of the activities associated with the stage of structure, assembly and casting of walls and slab, in a building in height. The system is modeled according to the way in which the project is executed by the builders and with the help of the balance lines, alternative scenarios are generated in order to compare the times and the average costs of completion of the project. In the first scenario, slack found in the current system is used in relation to the times of initiation of activities, without changing the amount of human resources and equipment. Secondly, the amount of human resources is slightly increased and the amount of formaletería equipment for walls and slab is increased by 25%. Based on the results, companies have a methodology for planning and selecting the appropriate scenario, according to their convenience.